2005
DOI: 10.1194/jlr.m500023-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for multiple complementary pathways for efficient cholesterol absorption in mice

Abstract: Apolipoprotein B (apoB)-dependent and apoBindependent pathways for cholesterol transport have been described in cultured cells. Here, we show that the apoBindependent pathway involves apoA-I-containing high density lipoproteins (HDLs). Cholesterol secretion by the HDLs, but not by the apoB pathway, was significantly reduced in primary enterocytes isolated from chow-and cholesterolfed apoA-I ؊ / ؊ mice. These enterocytes were capable of cholesterol efflux when apoA-I was provided extracellularly. In apoA-I ؊ / … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
86
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 52 publications
7
86
0
Order By: Relevance
“…ApoA-I interacts with ABCA1 and accepts FC in the first step, acts as a cofactor for LCAT in the second, and mediates interaction of HDL with SR-B1 in the third (6)(7)(8). Additionally, HDL and apoA-I play a significant role in cholesterol absorption (9), modulate endothelial function, inhibit platelet-activating factor synthesis, stimulate prostacyclin synthesis, bind to bacterial lipopolysaccharide, and inhibit low-density lipoproteininduced monocyte chemotaxis (10).…”
mentioning
confidence: 99%
“…ApoA-I interacts with ABCA1 and accepts FC in the first step, acts as a cofactor for LCAT in the second, and mediates interaction of HDL with SR-B1 in the third (6)(7)(8). Additionally, HDL and apoA-I play a significant role in cholesterol absorption (9), modulate endothelial function, inhibit platelet-activating factor synthesis, stimulate prostacyclin synthesis, bind to bacterial lipopolysaccharide, and inhibit low-density lipoproteininduced monocyte chemotaxis (10).…”
mentioning
confidence: 99%
“…Based on studies of the small intestine in neonatal mice, two groups of researchers proposed models for the assembly of Lpcat3-related apoB-containing lipoproteins (9,10). However, cholesterol secretion in cultured primary enterocytes is mediated by both apoB-dependent and -independent pathways (14). In this study, we found that Lpcat3 deficiency in primary enterocytes reduced not only cholesterol uptake (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…Primary Enterocyte Preparation and Plasma Membrane Isolation-Primary enterocytes were isolated according to two previous reports (14,16). The plasma membrane was isolated from primary enterocytes according to our protocol (17).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations